Partnered pharmacist charting on admission in the General Medical and Emergency Short‐stay Unit – a cluster‐randomised controlled trial in patients with complex medication regimens. (2nd June 2016) - Tong, E. Y.; Roman, C.; Mitra, B.; Yip, G.; Gibbs, H.; Newnham, H.; Smit, D. P.; Galbraith, K.; Dooley, M. J.
Summary: What is known and objective: Patients admitted to general medical units and emergency short‐stay units are often complex with multiple comorbidities, polypharmacy and at risk for drug‐related problems associated with increased morbidity and mortality. The aim of this study was to evaluate the effectiveness of a partnered pharmacist charting model completed at the time of admission to prevent medication errors. Methods: We conducted an unblinded cluster randomized controlled trial comparing partnered pharmacist charting to standard medical charting among patients admitted to general medical units and emergency short‐stay units with complex medication regimens or polypharmacy. This trial was conducted at an adult major referral hospital in metropolitan Melbourne, Australia, with an annual emergency department attendance of approximately 60 000 patients. The evaluation included patients' medication charts written in the period of 16 March 2015 to 27 July 2015. Patients randomized to the intervention were managed using the partnered pharmacist charting model. The primary outcome variable was a medication error identified by an independent assessor within 24 h of admission, who was not part of the patient's admission process. Results: Of the 473 patients who received standard medical staff charting during the study period, 372 (78·7%) had at least one medication error identified compared to 15 patients (3·7%) on the partnered pharmacist charting arm ( P < 0·001). The relative risk of an error with standard medical charting was 21·4 (95% CI: 13·0–35·0) with a number needed to treat (NNT) to prevent one error of 1·3 (95% CI: 1·3–1·4), and the relative risk of a high or extreme risk error with standard medical charting was 150·9 (95% CI: 21·2–1072·9) with a NNT to prevent one high or extreme error of 2·7 (95% CI 2·4–3·1). What is new and conclusion: Partnering between medical staff and pharmacists to jointly chart initial medications on admission significantly reduced inpatient medication errors (including errors of high and extreme risk) among general medical and emergency short‐stay patients with complex medication regimens or polypharmacy. Abstract : Polypharmacy has the potential to influence many aspects of safe prescribing, including adverse drug reactions, risk of medication interactions, and adherence. Managing patients with polypharmacy can be time consuming, with complex cases requiring careful balancing of competing clinical priorities and conflicting guidelines, and are often associated with errors in prescribing. Partnered pharmacist charting, with collaboration between a pharmacist and a medical officer on admission, significantly reduced medication errors (including high and extreme risk) on admission for general medical and emergency short stay patients with complex medication regimens or polypharmacy